LINGUISTIC CORPUS IN TEACHING FOREIGN LANGUAGES - Barnoyeva , N.Y (Innovative Development in Educational Activities, 2023)
This article focuses on relationship between corpus linguistics (CL) and language teaching (LT) and provide an overview of the most important pedagogical applications of corpora. While LT profits from the resources, methods, and insights provided by CL, it also provides important impulses that are taken up in corpus linguistic research. The present article will investigate what influence CL has had on LT so far, and in what ways corpora have been used to improve pedagogical practice. It will also discuss further possible effects of CL on LT .